Varieties of suffering in the clinical setting: re-envisioning mental health beyond the medical model - Wong, Paul T. P.; Laird, Don (Frontiers in Psychology, 2023)
In this paper, we argue for the need to rethink mental health beyond the medical model because much of human suffering cannot be diagnosed by the DSM-5. During the pandemic and post-pandemic, people have learned to accept the fact that no one is immune from suffering. Given the universality and complexity of human suffering, it is natural for people to wrestle with existential questions such as “Why struggle when all life end in death?” and “How can one flourish when life is so hard?” Existential positive psychology (EPP or PP2.0) was developed to address these existential concerns. After explaining the inherent limitations of the medical model and the need for EPP as an alternative vision for mental health, we provide illustrative clinical cases to demonstrate the advantages of this broader existential framework for both case conceptualization and interventions. According to EPP, mental illness is reconceptualized as both deficiency in knowledge and skills in coping with the demands of life and deficiency in meeting the basic needs for livelihood and mental health, the Soul’s yearnings for faith, hope, and love. Finally, we introduce integrative meaning therapy as a therapeutic framework which can equip people with the needed skills to achieve healing, wholeness, and total wellbeing.